Donor-derived cell-free DNA is associated with acute rejection and decreased oxygenation in primary graft dysfunction after living donor-lobar lung transplantation. Issue 1 (December 2018) - Tanaka, Shin; Sugimoto, Seiichiro; Kurosaki, Takeshi; Miyoshi, Kentaroh; Otani, Shinji; Suzawa, Ken; Hashida, Shinsuke; Yamane, Masaomi; Oto, Takahiro; Toyooka, Shinichi
Abstract Donor-derived cell-free DNA (dd-cf-DNA) has been shown to be an informative biomarker of rejection after lung transplantation (LT) from deceased donors. However, in living-donor lobar LT, because small grafts from blood relatives are implanted with short ischemic times, the detection of dd-cf-DNA might be challenging. Our study was aimed at examining the role of dd-cf-DNA measurement in the diagnosis of primary graft dysfunction and acute rejection early after living-donor lobar LT. Immediately after LT, marked increase of the plasma dd-cf-DNA levels was noted, with the levels subsequently reaching a plateau with the resolution of primary graft dysfunction. Increased plasma levels of dd-cf-DNA were significantly correlated with decreased oxygenation immediately (p = 0.022) and at 72 hours (p = 0.046) after LT. Significantly higher plasma dd-cf-DNA levels were observed in patients with acute rejection (median, 12.0%) than in those with infection (median, 4.2%) (p = 0.028) or in a stable condition (median, 1.1%) (p = 0.001). Thus, measurement of the plasma levels of dd-cf-DNA might be useful to monitor the severity of primary graft dysfunction, and plasma dd-cf-DNA could be a potential biomarker for the diagnosis of acute rejection after LT.